The Phenotypic Spectrum of 47 Czech Patients with Single, Large-Scale Mitochondrial DNA Deletions - Nicole Anteneová (Brain Sciences, 2020)
Background: In this retrospective study, we analysed clinical, biochemical and molecular genetic data of 47 Czech patients with Single, Large-Scale Mitochondrial DNA Deletions (SLSMD). Methods: The diagnosis was based on the long-range PCR (LX-PCR) screening of mtDNA isolated from muscle biopsy in 15 patients, and from the buccal swab, urinary epithelial cells and blood in 32 patients. Results: A total of 57% patients manifested before the age of 16. We did not find any significant difference between paediatric and adult manifestation in either the proportion of patients that would develop extraocular symptoms, or the timespan of its progression. The survival rate in patients with Pearson Syndrome reached 60%. Altogether, five patients manifested with atypical phenotype not fulfilling the latest criteria for SLSMD. No correlation was found between the disease severity and all heteroplasmy levels, lengths of the deletion and respiratory chain activities in muscle. Conclusions: Paediatric manifestation of Progressive External Ophthalmoplegia (PEO) is not associated with a higher risk of multisystemic involvement. Contrary to PEO and Kearns-Sayre Syndrome Spectrum, Pearson Syndrome still contributes to a significant childhood mortality. SLSMD should be considered even in cases with atypical presentation. To successfully identify carriers of SLSMD, a repeated combined analysis of buccal swab and urinary epithelial cells is needed.